(Effect of Banana Type, Amount and Duration Concentrate Storage Quality Against Soft Drinks Fruit Banana) - Indra Neffi Ridwan; Eppy Susanto; F.G. Winarno (Warta Industri Hasil Pertanian, 1987)
The research was aimed at studying the effect of banana variety, amount of concentrate and lenght of storage on the quality of soft drink made of banana juice. The result showed that banana of "AMBON" variety produced soft drink of more preferable taste, clearer and higher acid content. The higher the amount of concentrate, the higher the total soluble solid, total acid and total sugar. The clarity decreased as the amount of concentrate was increased from 12% to 16% and tend to be constant of the increased from 16% to 20%. Total soluble solid and total sugar increase until the fourth week and will decreased later. The longer the storage, the lower its clarity